(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2016)
The emerging drift in contemporary media scenario has witnessed a transition in the way information, ideas; opinions are transmitted, shared, exchanged and interchanged. The sustainable change in media landscape has remarkably changed the eco system of information delivery, leading newspapers and news channel are taking to digital journalism in a big way. The speedy technical progress, which print media is adapting to continue, has brought about far reaching changes in the modern media set-up. The onslaught of technology is changing the dynamics of news delivery too, newspaper once the medium for breaking news, surrendered that role to TV and internet could take it over. This paper tries to describe how crudely the news eco system is shifting and it presently looks like the Net breaks the news, TV is doing the follow ups and live coverage and newspapers end up doing analyses. Digital media gives access of information at the touch of a mouse bottom. In an interdependent world, Digital media is making worldwide communication a reality. The worldwide web is a challenge to traditional news practices because of its interactive opportunity that offers for instant communication and is competing ahead at a Remarkable speed, irrespective of any demography or geographical boundary. This paper attempts to explain that digital Media has brought the world closer globally. Among the information revolution, Digital media has become such an integral part of our lives and plays impactful role in society.